Criminological Assessment of Medical Misconduct during the COVID-19 Pandemic - Inshyn, Mykola; Sainetsky, Oleg; Melnyk, Volodymyr; Hubs'ka, Olena; Dzhura, Khrystyna (International Journal of Criminology and Sociology, 2022)
This study examines the professional actions of health workers during the spread of the COVID-19 pandemic from the point of view of criminological assessment in the context of labor relations. With the help of political and legal analysis and a comparative legal method, the work considers the international practice of assessing the actions of medical workers from the standpoint of criminal responsibility, political and legal initiatives concerning the protection of the rights of medical workers during the spread of a pandemic and quarantine measures. This study argues for significantly broader criminal immunity for health workers during a pandemic. At the same time, the study gives grounds to assert that today the lack of sufficient empirical data and research complicates an objective assessment of the offender. At the same time, based on the results of this study, it is suggested that in the near future the number of investigations and appeals to the court on issues related to the professional activities of medical workers carried out during the spread of the pandemic will increase..